The influence of CG technology on the aesthetics of Chinese magic films take the candle in the tomb film series for example / Shibo Zhou, Md Nagib Padil and Mohd Nasiruddin Abdul Aziz - Shibo, Zhou; Padil, Md Nagib; Abdul Aziz, Mohd Nasiruddin (Universiti Teknologi MARA, Perak, 2024)
This study aims to investigate the impact of computer-generated imagery (CG) on the aesthetic context and innovation of oriental gods and creatures in Chinese magical film footage. This study focuses on the analysis and research of CG technology in Chinese magical film lens images, as well as the aesthetic habits and aesthetic psychology of contemporary audiences towards oriental gods and creatures. This research employs a qualitative research approach because it is appropriate for examining the cultural background and aesthetic habits of Chinese magical film lens images created using CG technology, as well as the aesthetic emotions that the film evokes in its audience. This study specifically examines the aesthetic expression and breakthrough innovation of oriental gods and monsters in the CG screen effects of the film series Candle In The Tomb, as well as the operation process of Chinese magical film CG technology and its expression based on and the generative context and breakthrough innovation of oriental gods' aesthetic style. This study will provide a theory of the CG technology used to guide the visual aesthetics of Chinese fantasy films. It will benefit creators of Chinese magic films, researchers, academicians, students, and those interested in the subject's study and preservation.